History Of Burgerlijk Wetboek In Indonesia - Hanna Wijaya; Yohanes Firmansyah; Yana Sylvana; Michelle Angelika S (Jurnal Indonesia Sosial Sains, 2021)
Civil Law is a provision that regulates the rights and interests of individuals in society. The history of the development of civil Law in Indonesia cannot be separated from the history of legal science development in other European countries. Law in Indonesia is a mixture of European legal systems, religious Law, and customary law. Most of the systems adopted, both civil and criminal, are based on continental European Law. This study uses a research methodology that reviews normative juridical studies conducted by synthesizing deductive conclusions from statements in data sources such as library materials including journals, books, documents, and literature or secondary Law such as laws, legal theory, court decisions, relevant expert opinion and related to the discussion in this journal. This research is an analytical prescriptive that synthesizes data, analyzes, and concludes qualitatively. Civil Law in Indonesia comes from the Dutch language, namely Burgerlijk Recht, derived from the Burgerlijk Wetboek (B.W), which in Indonesia is known as the Civil Code (KUH Perdata). Civil Law in Indonesia is somewhat different from the civil Law that applies in the Netherlands. Burgelijk Wetboek's systematics consists of Van Personen, Van Zaken, Van Verbintenissen, Van Bewijaeu Veryaring.